A MODEL PROPOSAL FOR KEEPING REFLECTIVE JOURNAL IN TRANSLATION STUDIES COURSES - BARUT, Evren; BAYTAR, İlknur (ASOS Yayinevi, 2024)
Keeping a reflective diary/journal is a method that has been used in many disciplines recently, because it provides some opportunities for teachers and students to observe their learning and teaching processes. Teachers use reflective journals to help students become aware of their own learning processes and to gain insights into the students' thoughts and understanding. Besides, it helps to develop students' self-awareness and critical thinking. However, the literature review reveals a limited number of studies focusing on the use of the reflective diary method in translation classes. Therefore, this study aims to contribute to translation studies by presenting a model to use the reflective journal method in translation classes. To achieve this, information about reflective journals will be given in the first part of the article. Then, the study aims to give information about the benefits and drawbacks of the reflective journaling method. In addition, previous studies on the use of reflective journals in different contexts will be presented. Finally, a sample model for how to keep reflective journal in translation classes will be proposed to support teachers to adopt this method in translation courses.